Social Media Advertising Marketing Strategies in Determining Purchase Decisions - Firly Adhyatma Rusdi; Cristina Margaretta; Muhammad Aras (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The development of the business world has progressed rapidly to encourage increased competition between companies. Building a successful business is not as easy as turning the palm of your hand. Although it is difficult, business actors must be able to manage marketing strategies to determine purchasing decisions for the products/services offered. The purpose of this study is to examine advertising marketing strategies on social media in determining purchasing decisions. This type of research uses a literature study with a qualitative approach. Sources of data are obtained through articles, books, and other documents relevant to the research to help strengthen theories and phenomena of relationships or effects between variables. The qualitative approach emphasizes the aspect of exploring each variable to obtain independent information, placing more emphasis on the quality of the information extracted. The results of this study are advertising marketing strategies on social media influence in determining purchasing decisions. Determination of strategy in marketing related to purchasing decisions explained that technology brought major changes that previously worked manually and had begun to be developed digitally. Lifestyle changes supported by technological developments have an impact on shifting conventional advertising strategies to the digital world at this time, namely on social media which the majority of people use. Suggestions, every change that occurs must be able to be read by business actors to maintain and develop their business. Therefore, the marketing strategy must be planned as well as possible and know the vision, mission, and achievements to be carried out.